Residence at moderately high altitude and its relationship with WHO Group 1 pulmonary arterial hypertension symptom severity and clinical characteristics: the Pulmonary Hypertension Association Registry. (November 2020) - Fakhri, Shoaib; Hannon, Kelly; Moulden, Kelly; Peterson, Ryan; Hountras, Peter; Bull, Todd; Maloney, James; De Marco, Teresa; Ivy, Dunbar; Thenappan, Thenappan; Sager, Jeffrey S.; Ryan, John J.; et al.
Background: WHO Group 1 pulmonary arterial hypertension is a progressive and potentially fatal disease. Individuals living at higher altitude are exposed to lower barometric pressure and hypobaric hypoxemia. This may result in pulmonary vasoconstriction and contribute to disease progression. We sought to examine the relationship between living at moderately high altitude and pulmonary arterial hypertension characteristics. Methods: Forty-two US centers participating in the Pulmonary Hypertension Association Registry enrolled patients who met the definition of WHO Group 1 pulmonary arterial hypertension. We utilized baseline data and patient questionnaire responses. Patients were divided into two groups: moderately high altitude residence (home ≥4000 ft) and low altitude residence (home <4000 ft) based on zip-code. Clinical characteristics, hemodynamic data, patient demographics, and patient reported quality of life metrics were compared. Results: Controlling for potential confounders (age, sex at birth, body mass index, supplemental oxygen use, race, 100-day cigarette use, alcohol use, and pulmonary arterial hypertension medication use), subjects residing at moderately high altitude had a 6-min walk distance 32 m greater than those at low altitude, despite having a pulmonary vascular resistance that was 2.2 Wood units higher. Additionally, those residing at moderately high altitude had 3.7 times greater odds of using supplemental oxygen. Conclusion: Patients with pulmonary arterial hypertension who live at moderately high altitude have a higher pulmonary vascular resistance and are more likely to need supplemental oxygen. Despite these findings, moderately high altitude Pulmonary Hypertension Association Registry patients have better functional tolerance as measured by 6-min walk distance. It is possible that a "high-altitude phenotype" of pulmonary arterial hypertension may exist. These findings warrant further study.